Total Knee Arthroplasty: Superiority of Intra-Articular Tranexamic Acid Over Intravenous and Cell Salvage as Blood Sparing Strategy – A Retrospective Study - Coelho M; Bastos C; Figueiredo J (Journal of Blood Medicine, 2022)
Miguel Coelho, Catarina Bastos, Jose Figueiredo Anesthesiology Department, Centro Hospitalar do Baixo Vouga, Aveiro, PortugalCorrespondence: Miguel Coelho, Anesthesiology Department, Centro Hospitalar do Baixo Vouga, Av. Artur Ravara, Aveiro, 3810-164, Portugal, Tel +351 914397295, Email Miguel.apc90@gmail.comPurpose: Total knee arthroplasty is associated with considerable perioperative hemorrhage. The decrease in hemoglobin concentration and the need for allogenic blood transfusion are related to increased morbidity and mortality. Strategies for minimizing perioperative bleeding are used, such as tranexamic acid and cell salvage. The study aimed to compare intravenous, intra-articular tranexamic acid and cell salvage protocols regarding perioperative hemoglobin variation. Secondary outcomes included blood loss; allogenic transfusions; complications and in-hospital stay.Patients and Methods: Patients submitted to unilateral total knee arthroplasty between January and December 2018 were retrospectively evaluated. After excluding 62 patients, 204 were subdivided into 3 groups according to the protocol used. Statistical analysis was performed with SPSS version 26.0. One-way ANOVA and Kruskal–Wallis tests were used. Considered a p-value of < 0.05 for statistical significance.Results: Variation of hemoglobin in the intra-articular tranexamic acid group was significantly lower than that of intravenous (p < 0.001) and cell salvage (p = 0.001) groups. Blood loss, variation of hematocrit, need for blood transfusion and in-hospital stay were also statistically significantly lower in the intra-articular tranexamic acid group. The only related complications were in the intravenous tranexamic acid group. No thromboembolic complications were identified which further solidifies the safety of tranexamic acid administration.Conclusion: This data shows superiority of the intra-articular administration of tranexamic acid over the other techniques in total knee arthroplasty. We propose this protocol as an efficient, low-risk blood-sparing strategy.Graphical Abstract: Keywords: arthroplasty, knee, acid tranexamic, salvage, transfusion